Traffic : nadie puede escapar - Soderbergh, Steven, 1963- (Barcelona Manga Films, 2000)
A conservative judge is appointed by the President to spearhead America's escalating war against drugs, only to discover that his teenage daughter is an addict.
No recomendada para menores de 13 años
Idiomas : castellano e inglés. Subt. : castellano e inglés
Michael Douglas, Benicio Del Toro, Catherine Zeta-Jones
Keywords: Películas cinematográficas -- DVD